Report of the field work for the evaluation of the risk due to the flow of debris caused by anomalous precipitations in the A.H. “César Vallejo” and A.H. “Children of Saldaña”, District of Comas, Province of Lima, Department of Lima - Delgado Estrada, Juan Manuel (2021)
The present work corresponds to an evaluation of disaster risks that was carried out in the AH Cesar Vallejo and the AH Hijos de Saldaña, in the district of Comas. To collect the necessary information, the geospatial data available from the competent institutions were used, which were subsequently processed with the support of GIS software: ArcMap; as well as primary sources, which in this case were the surveys carried out on the residents of these human settlements. After the field and office work, it was found that the risk levels in many of the properties ranged between high and very high, for which the prompt implementation of corrective and preventive measures is necessary.